2020
DOI: 10.1136/neurintsurg-2019-015702
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral aneurysm treatment trends in National Inpatient Sample 2007–2016: endovascular therapies favored over surgery

Abstract: BackgroundFlow modulation is the newest endovascular technique for treatment of cerebral aneurysms.ObjectiveTo investigate changes in aneurysm treatment practice patterns in the USA.MethodsFrom the 2007 to 2016, the National Inpatient Sample databases, hospital discharges associated with unruptured aneurysms (UA), and/or ruptured aneurysms (RA) having undergone surgical clipping (SC) and/or endovascular treatments (EVT) were identified using the International Classification of Diseases codes. Patient demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 11 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…Over the past decade, there has been much effort made to identify the best treatment for ruptured and unruptured IA, such as clipping or endovascular treatment (EVT), coiling, or stenting. Technological innovations and advancements in the neuroendovascular space shifted the standard for treating IA from open surgical approaches to endovascular therapies ( 24 ). EVT was mentioned in four articles in the top 10 most-cited articles and three co-cited references with the highest citation bursts (ending in 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, there has been much effort made to identify the best treatment for ruptured and unruptured IA, such as clipping or endovascular treatment (EVT), coiling, or stenting. Technological innovations and advancements in the neuroendovascular space shifted the standard for treating IA from open surgical approaches to endovascular therapies ( 24 ). EVT was mentioned in four articles in the top 10 most-cited articles and three co-cited references with the highest citation bursts (ending in 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The fibrin-based FD coating did not induce thrombosis angiographically or histologically and had no adverse effects on the rate of re-endothelialization. Known complications after FD treatment such as stent thrombosis and to a lesser extent in-stent stenosis remain limiting factors of this treatment [ 19 ]. The present study investigated these limiting factors that have prevented FDs from being used in broader patient populations or in critical situations such as the treatment of acutely ruptured aneurysms [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The past few decades have seen a gradual shift from open surgery to endovascular therapies for the treatment of both ruptured and unruptured aneurysms in the USA. 22 Although coils are the archetypical device for endovascular aneurysm treatment and provide a safe and effective therapy for many aneurysms, wide-necked and large or giant aneurysms are still a major challenge. In addition, Fujiwara and Kallmes 23 found that coil embolization led to occasional coil compaction in one of 17 cases (6%) and Dai et al 24 found this to occur in three of 18 cases (17%), both using the same animal model.…”
Section: Discussionmentioning
confidence: 99%